The imagined electric vehicle user: Insights from pioneering and prospective buyers in Milton Keynes, United Kingdom. (June 2019) - Valdez, A.M.; Potter, S.; Cook, M.
Highlights: Pro-EV Interventions are driven by two user imaginaries: narrow rationality and sensemaking. Rational approaches use incentives and infrastructure so users can optimize existing systems. Sensemaking approaches empower users to create new business models, institutions and practices. Sensemaking approaches frame barriers to EV adoption as informational, not technical or financial. Rational users found subsidies insufficient, sensemakers found viable strategies for EV adoption. Abstract: This research explores how socio-technical imaginaries about electric vehicles and their users developed in the context of the Plugged-in Places programme in Milton Keynes, UK. Collectively imagined forms of social life and social order are reflected in the design and fulfilment of scientific and technological projects as imagined futures shape the technological search space and influence social responses to innovation (Jasanoff and Kim, 2009, 2013). This research focuses on the imaginaries of pioneering and prospective adopters of EVs in business organizations in Milton Keynes. The imaginaries of organizational buyers and fleet managers subtly shaped their exploration of early-market vehicles as they articulated the demands, barriers and motivations of users within their firm. This research draws on a thematic analysis of interviews with business and governmental actors, policy documents and trade literature discussing the early-market adoption of EVs by business organizations. The results identify the processes through which business adopters make sense of the new technology as well as the policies and organizations that supported their learning process. In addition to technical concerns, key aspects concerned patterns of use and demand, fitness for operations, and new business and operational models suited to the characteristics of EVs. Thus, it is concluded that the imaginaries of business adopters and of the organizations supporting them increasingly envision adopters not just as rational optimizers but also as complex problem solvers working out new ways to embed EVs in innovative, competitive configurations that work for them.